Pengaruh Rasio Etanol dan Air Cucian Surimi Ikan Gabus (Channa striata) Terhadap Recovery Protein Larut Air - Nurhadi Wiranata; Ace Baehaki; Susi Lestari (Universitas Sriwijaya, 2015)
The objective of this research was to know the deposition of protein in snakehead fish (Channa striata) surimi wash water and know the effect of the ratio of ethanol and surimi wash water from snakehead fish (Channa striata) on the recovery of protein water solubility. Design was used with two factors of treatment which were repeated twice. The factors of treatment consist of surimi wash frequency and the addition of ethanol concentration. The parameters observed were water-soluble protein analysis and SDS-PAGE analysis. The highest precipitation in the treatment T2, while the lowest precipitation in treatment T0. Based on BJND test, every treatment showed different precipitated with other treatments. In each sample the water-soluble protein content (PLA) in the first washing is greater than the second washing. Based on BJND test, treatment T1, T2, and T3 were not different but significantly different with treatment T0 (without ethanol). The treatment effect of the ratio of ethanol and surimi wash water from snakehead fish effect on the percentage of water-soluble protein content. SDS-PAGE analysis showed treatment P1T0, P1T1, and P2T0 still contains albumin with a molecular weigh of 68.75 kDa. Results recovery of protein from the ratio effects of ethanol and snakehead fish surimi wash water from showed thet the use of ethanol is able to precipitate proteins. The use of ethanol is added to snakehead surimi wash water serves as a coagulant.